ANALYSIS OF THE HEALTH STATUS OF SCHOOL-AGE STUDENTS - Sadullayeva X. A.; Sadirova M. K.; Jalolov N.N. (The Conference Hub, 2025)
School-age children experience a critical period of physical and psychological development. During this period, their health status has a significant impact on their educational process, intellectual development, and social life in general. Therefore, it is important to analyze the health of school-age children and develop measures to improve it.The study used statistical analysis, questionnaires, medical examination results, and scientific articles to identify the main types of health problems among schoolchildren and study their causes.